2016
DOI: 10.1155/2016/9747863
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydro-iso-alpha Acids Antagonize Estrogen Receptor Alpha Activity in MCF-7 Breast Cancer Cells

Abstract: Tetrahydro-iso-alpha acids commonly called THIAA or Tetra are modified hop acids extracted from hop (Humulus lupulus L.) which are frequently used in brewing industry mainly in order to provide beer bitterness and foam stability. Interestingly, molecular structure of tetrahydro-iso-alpha acids is close to a new type of estrogen receptor alpha (ERα) antagonists aimed at disrupting the binding of coactivators containing an LxxLL motif (NR-box). In this work we show that THIAA decreases estradiol-stimulated proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It has long been known that secondary metabolites, which are secreted from the lupulin glands of female hop cones (but are also present in male inflorescences at a low concentration), are groups of compounds that are not synthesized by humans but are valuable to human life, especially for the beer-brewing industry and human health. , Among these metabolites, the resinous compounds can be classified as bitter acids, polyphenols, and volatile oil. The volatile oil comprises mainly terpenoids and possesses moderate antibacterial effects against the Gram-positive bacteria Enterococcus , Bacillus subtilis , and Staphylococcus aureus and the Gram-negative bacteria Escherichia coli , Clostridium perfringens , Enterococcus faecalis , and Staphylococcus aureus subs , as well as an antifungal effect against the fungus Trichophyton interdigitale and the yeast Candida albicans . , However, the present review focuses on the effects of hop bitter acids and lupulin-associated polyphenols (especially xanthohumol), which have been reported to exert a wide range of anticancer effects and to prevent chronic diseases, as a chemotherapeutic modality, both in vitro and in vivo. …”
Section: Identification Of Nutritional Factors In H Lupulusmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that secondary metabolites, which are secreted from the lupulin glands of female hop cones (but are also present in male inflorescences at a low concentration), are groups of compounds that are not synthesized by humans but are valuable to human life, especially for the beer-brewing industry and human health. , Among these metabolites, the resinous compounds can be classified as bitter acids, polyphenols, and volatile oil. The volatile oil comprises mainly terpenoids and possesses moderate antibacterial effects against the Gram-positive bacteria Enterococcus , Bacillus subtilis , and Staphylococcus aureus and the Gram-negative bacteria Escherichia coli , Clostridium perfringens , Enterococcus faecalis , and Staphylococcus aureus subs , as well as an antifungal effect against the fungus Trichophyton interdigitale and the yeast Candida albicans . , However, the present review focuses on the effects of hop bitter acids and lupulin-associated polyphenols (especially xanthohumol), which have been reported to exert a wide range of anticancer effects and to prevent chronic diseases, as a chemotherapeutic modality, both in vitro and in vivo. …”
Section: Identification Of Nutritional Factors In H Lupulusmentioning
confidence: 99%
“…Oral administration of 0.1% tetrahydro- or hexahydro-iso-α-acids for 6 weeks to diethyl nitrosamine-induced male Wistar rats (body weight 180–190 g) with hepatocellular carcinoma, which is the third leading cause of cancer-related deaths globally, because of alcohol, nonalcoholic steatohepatitis, hepatitis B, and hepatitis C infection, resulted in the reduction of the transformation marker glutathione- S -transferase-positive areas and tumor numbers in the liver compared to the diethylnitrosamine treated control rats. , In another study, tetrahydro-iso-α-acids inhibited estrogen receptor-alpha transcriptional activity, induced a 75% decrease in metabolic activity measured by the MTT assay, and reduced the proliferation of Michigan Cancer Foundation-7 (MCF-7) breast cancer cells, based on the reversal of the effect of 17β-estradiol on cell cycle progression and then a slowdown of the cell cycle . Rho-iso-α-acids, prepared from a modified hop extract, have been shown to potently and selectively inhibit iCOX-2-stimulated prostaglandin E 2 biosynthesis, with minimal effects on cyclooxygenase (COX)-1 or COX-2, in lipopolysaccharide-induced mouse macrophage RAW 264.7 cells (IC 50 of COX-1 was 289 μg/mL, IC 50 of COX-2 was 1.3 μg/mL) (Hall et al, 2008).…”
Section: Bitter Acidsmentioning
confidence: 99%
“…Both ERα and ERβ bind co-factor proteins through LxxLL motifs. It is reported that tetrahydro-iso-alpha acid inhibits the estrogen-stimulated transcriptional activity of ERs by interfering with the binding of ERs to LxxLL motifs in breast cancer cell line MCF-7 [ 102 , 103 ]. One of the enzothiophenone derivatives also has an inhibitory action on the binding of ERα to LxxLL, and the compound also represses the transcription of the mutant form of ERα gene (ESR1) [ 104 ].…”
Section: Future Perspectives On Exploring Ppi In Hormone-dependentmentioning
confidence: 99%
“…In today’s society, breast cancer is one of the most common and lethal cancers. Estrogen receptors have a close correlation with the development of breast cancer, and according to related studies, estrogen receptor alpha (ERα) in estrogen has a strong promoting effect on the dominant characterization of breast cancer ( Lempereur et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%